(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
Human resources have become an important economic factor, especially as a key of competitiveness. The main point of knowledge – based economy is the employable skill, and the resource of the progression is its extracting innovation. Vocational training system is probably the most important field of human resources’ extraction. The companies had to face a lot of problems in , young” market economy, included the process of skilled and employable workers" covering. The present Government is committed to the so-called dual system of vocational training, that means besides the theoretical part of the education the students take a well-organized and usable practice at companies, covering the relationship with the special student contract. The Hungarian Chambers create a national survey in every year about the companies’ claims related to labour market, and expected skills of graduates. This presentation focuses on the survey’s results in 2011, especially on the specialities and features of the vocational practice activities. The Chambers completed the survey involving 2000 companies, to face the companies’ opinion and motivation related to vocational practice activities, and to identify the most specific problems in this process.